Too much but not enough: Issues of water management in Albania in light of climate change - Klodjan Rama (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2016)
This study aims at analysing the major issues concerning Albania's water sector. Albania's natural conditions are characterised by abundant quantities of water resources, often too much. Yet, the demands of, especially, the agricultural sector are still not fully met. [...] – – Das Ziel der Studie ist, die wichtigsten Probleme bezüglich des albanischen Wassersektors zu analysieren. Albanien ist durch ein natürliches Wasserreichtum gekennzeichnet - oft sogar durch Wasserüberschuss. Dennoch kann der Wasserbedarf, insbesondere des Agrarsektors, nicht vollständig gedeckt werden. [...]
urn:nbn:de:gbv:3:2-69165
Keywords: 330